Utilization of blood and blood components in the department of clinical hematology of a tertiary care hospital: A prospective hospital-based study - Rubiya Ryhan; Mohd Zubair Qureshi; Fayaz Ahmad Bhat; Rumana H Makhdoomi; Reashma Roshan; Afaq Ahmad Khan; Sajad Ahmad Rather; Kaneez Fatima (Asian Journal of Medical Sciences, 2024)
Background: To have proper utilization of blood and its components adherence to established guidelines is essential. Hence, periodic review of blood components is necessary to improve transfusion practices and decrease the inappropriateness of blood components.Aims and Objectives: Our study aims to assess the utilization and appropriateness of blood and blood components in the Department of Clinical Hematology SKIMS, Soura, Srinagar.Materials and Methods: This prospective observational study was conducted in the Department of Blood Transfusion and Immunohematology, SKIMS, Soura, Srinagar, over a period of 1 year from August 2020 to July 2021 on patients admitted in Clinical Hematology requiring transfusion therapy. The number of all blood and blood component units supplied over a period of 1 year was assessed. The usage of different types of blood component was recorded and correlated with the patient’s diagnosis and indications for transfusion.Results: A total of 250 patients were transfused with 2099 blood and blood components, among them 64.32% (1350) units were used appropriately and 35.68% (749) units were used inappropriately. Transfusions of packed red blood cells were found to be inappropriate in patients with asymptomatic chronic anemia with Hemoglobin >7 g/dL. Fresh frozen plasma was given inappropriately in cases of bleeding without derangement of coagulation tests. Inappropriate use of platelets was seen in patients who had received platelets prophylactically with platelet count above 10,000/μL.Conclusion: Proper implementation of guidelines for the use of various blood components would help reduce their inappropriateness.